Rancang Bangun Sistem informasi Pengawasan Intern dan Pemantauan Tindak Lanjut Siap Mental Menggunakan Framework Laravel - Ayupratiwi, Pramesti; Retnoningsih, Dwi; Fitriyadi, Farid (Institut Teknologi Garut, 2025)
The Klaten Regency Government is currently facing problems related to the lack of utilization of technology in supervising SKPD activities because it still uses manual methods, namely recording supervision in books or spreadsheets which causes delays, recording errors and difficulties in finding follow-up data findings. This research aims to design and build a laravel-based follow-up supervision and monitoring system for local government agencies. The system development method using Waterfall includes the stages of needs analysis, system design, implementation and testing. The results of blackbox testing show that the system functionality is in accordance with the percentage of 100% without any errors. In addition, the results of usability testing with the dimensions of usefulness, ease of use, ease of learning and satisfaction show the results of the usability level of 97% and are categorized as very feasible so that the system proves to be easy to use, easy to learn and has satisfied users. So based on these results, it is hoped that this system can help accelerate supervisory monitoring and increase the transparency of regional agency governance.